Response to Uncertain Threat in Acute Trauma Survivors - (:unkn) unknown (My University, 2020)
Uncertainty is often associated with subjective distress and a potentiated anxiety response. The heightened response to uncertainty may be a central mechanism via which anxiety-, trauma-, and stressor-related disorders are developed and maintained. The current study compared the neural response to predictable and unpredictable threat in acute trauma survivors to clarify the role of the response to uncertain threat in fear circuitry and further inform the nature of the development of PTSD in the context of uncertain threat. The novel study showed that anticipating unpredictable (primarily negative images) relative to predictable images increased activation in a frontoparietal network and was associated with decreased acute trauma symptoms, suggesting this network may be associated with an adaptive mechanism for responding to unpredictable threat. Results also showed increased PTSD symptoms was associated with more sustained activation during unpredictable vs. predictable blocks in the insula. Additionally, those with more severe PTSD symptoms had greater response to transient relative to sustained unpredictable (vs. predictable) conditions in the superior frontal gyrus. These findings extend previous work highlighting the insula’s role in sustained responsivity to unpredictability in anxiety disorders and PTSD to symptomatology in acute trauma survivors. Finally, widespread sustained activation of predominantly frontocentral and frontoparietal regions in unpredictable relative to predictable blocks was associated with increased intolerance of uncertainty.
Keywords: fMRI; PTSD; Threat; Trauma; Uncertainty; Unpredictable